Diverging diamond interchanges: A driving simulator study. (May 2020) - Meuleners, Lynn B; Roberts, Paul
Highlights: The Diverging Diamond Interchange (DDI) is a novel interchange design. A driving simulator study compared driving on a DDI to a standard intersection. Compliance to speed limit was poorer on the DDI than the standard intersection. A higher proportion of red-light violations were observed on the DDI. No other significant differences in driving performance measures were observed. Overall, Australian drivers had minimal difficulties negotiating the DDI. Abstract: This study assessed driver performance while navigating a Diverging Diamond Interchange (DDI) compared to a standard intersection in a driving simulator. A total of 201 Western Australian (WA) drivers aged 18–80 years completed the simulator drive and questionnaire. Measures of driving simulator performance assessed included time spent out of lane, number of lane excursions, compliance to the speed limit, crashes and near misses. Other driving measures, which were recorded by the researcher, included driver errors/violations such as red-light violations, wrong way violations and navigation errors. Qualitative information was also obtained in a post exit interview with each participant regarding the difficulties they experienced when driving through the DDI. A repeated-measure analysis of variance (r-ANOVA) was undertaken to examine differences in intersection type (DDI versus standard intersection) and driving performance measures from the driving simulator. The only significant result was compliance to the speed limit (F (1, 656) = 160.11,  p < 0.001) on the driving simulator. A higher proportion of red-light violations were observed by the researcher as participants navigated through the DDI, compared to the standard intersection. Qualitative comments from participants also highlighted the need for better signage and road markings. Recommendations when DDIs are implemented include community education on speed limit compliance, avoidance of red-light violations and design improvements regarding signage and road markings.